PIC Detector for Piano Chords. (19th October 2010) - Barbancho Barbancho, Ana M. Ana M.; Tardón Tardón, Lorenzo J. Lorenzo J.; Barbancho Barbancho, Isabel Isabel
Abstract : In this paper, a piano chords detector based on parallel interference cancellation (PIC) is presented. The proposed system makes use of the novel idea of modeling a segment of music as a third generation mobile communications signal, specifically, as a CDMA (Code Division Multiple Access) signal. The proposed model considers each piano note as a CDMA user in which the spreading code is replaced by a representative note pattern. The lack of orthogonality between the note patterns will make necessary to design a specific thresholding matrix to decide whether the PIC outputs correspond to the actual notes composing the chord or not. An additional stage that performs an octave test and a fifth test has been included that improves the error rate in the detection of these intervals that are specially difficult to detect. The proposed system attains very good results in both the detection of the notes that compose a chord and the estimation of the polyphony number.